2022
DOI: 10.21834/ebpj.v7i20.3452
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of Transit-Oriented Development with Land Use Planning

Abstract: The ineffectiveness of public transport discourages participation from the public. Thus, the transportation systems and land use planning need to be more practical. This study explores the land use criteria that need to be considered while planning rail-based transit-oriented development (TOD). The method systematically reviewed the land use characteristics for transit-oriented development. Thematic Analysis was employed by applying scoping techniques. The result showed a network mapping of the interrelation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, urban planning faces challenges in many cities worldwide in terms of effectively planning and improving the built environment to support sustainable transport (Hrelja et al, n.d.). Previous research has demonstrated that land use significantly affects people's travel pattern (Abdullah et al, 2022). It is also apparent that cities that have boosted public transportation ridership increased walking and cycling, decreased land consumption and dependence on cars have done so because land use and transportation planning have been integrated (Van Lierop et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, urban planning faces challenges in many cities worldwide in terms of effectively planning and improving the built environment to support sustainable transport (Hrelja et al, n.d.). Previous research has demonstrated that land use significantly affects people's travel pattern (Abdullah et al, 2022). It is also apparent that cities that have boosted public transportation ridership increased walking and cycling, decreased land consumption and dependence on cars have done so because land use and transportation planning have been integrated (Van Lierop et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Method of Study Source: Adapted fromWestphaln et. al (2021);Abdullah et al (2022b);Jamaluddin et al (2023) Figure7above shows the scoping review process adapted fromWestphaln et al (2021),Abdullah et al (2022b), andJamaluddin et al (2023) to gather the data in reviewing the literature. Four (4) steps have been conducted to review the literature, starting by determining the topic of study, which is ''low carbon governance''.…”
mentioning
confidence: 99%